Surgical Options in Managing Convergent Strabismus Fixus Related to High Myopia - Jessica Zarwan; Gusti G Suardana; Anna P Bani (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2015)
Â Background: Convergent strabismus fixus is a condition in which one or both eyes are anchored in extreme adduction. This condition is caused by superotemporal herniation of the enlarged globe from the muscle cone through the space between the superior and lateral rectus muscle. It is commonly related to high myopia. Recently, transposition type procedure which unite the superior and lateral rectus muscles were proposed as the treatment of choice in this condition. However, there is no clear consensus regarding the best surgical procedure in convergent strabismus fixus. This case series reported three rare cases of convergent strabismus fixus related to high myopia and highlight the option of surgical procedure that can be done in these cases. Case Illustration: Three patients presented with convergent strabismus fixus of both eyes with history of bilateral high myopia since childhood. All patients showed Krimsky tests of >95Î”ET preoperatively, with medial displacement of superior rectus and inferior displacement of lateral rectus of both eyes in all patients on orbital imaging. The bilateral Yokoma procedure both resulted in an orthophoric postoperative result with marked improvement in abduction and elevation. The hemi-Jensen also showed a significant improvement of over than 60Î” on the operated eye, resorting it to a central position during primary gaze. Conclusion: Convergent strabismus fixus is a rare condition and frequently associated with high myopia. Both techniques of Yokoyama procedure or hemi-Jensen procedure combined with medial rectus recession showed similar good results with improvement in position and ocular motility of the eye Keywords: convergent strabismus fixus, high myopia, Yokoyoma procedure, hemi-Jensen procedure